A Scientometric Review Summarizing the Impact of Nanomaterials on the Fresh, Hardened, and Durability Properties of Cement-Based Materials - Shayan Ali Khan; Hassan Amjad; Farhan Ahmad; Hammad Anis Khan (Advances in Civil Engineering)
Nanomaterials have emerged as a revolutionary force in the realm of cement-based materials (CBMs), opening new horizons for the construction industry. This comprehensive review delves into the synthesis, dispersion mechanisms, and profound impacts of nanomaterials on the properties of CBMs. This paper explores the synthesis and dispersion of nanomaterials, shedding light on the diverse techniques used to synthesize nanoscale particles for specific applications in CBMs. It emphasizes the significance of achieving consistent dispersion to fully harness the potential of these materials. In the following section, our focus shifts to the transformative impact of nanomaterials on various aspects of CBMs. Notably, nanomodified CBMs experience significant improvements in their hydration kinetics, mechanical characteristics, rheological properties, and thermal resistance, all of which are discussed in detail. Moreover, self-healing cementitious composites employing nanomaterials offer innovative strategies for addressing remedies for structural deterioration with time. While the potential of nanomaterials is promising, it is crucial to exercise caution due to concerns about potential health risks. While nanomaterials have shown promise in enhancing the mechanical properties of cementitious materials, future research endeavors will focus on their potential to create multifunctional concrete with applications extending beyond simple load-bearing capacity. This study concludes with a look into the future, imagining the inclusion of nanomaterials into civil infrastructure applications such as 3D printing, sustainable construction, and smart materials.